The Effect of the Ethno-RME Learning Model on Improving HOTS and Self-Efficacy of Elementary School Students - Putik Rustika; Rifqi Hidayat (CV. Akademi Merdeka, 2026)
Mathematics learning in elementary schools is still largely abstract, as it focuses on memorizing formulas and procedures without involving cultural contexts that are close to students’ daily lives. This condition leads to low levels of higher-order thinking skills (HOTS) and self-efficacy. This study aims to examine the effect of applying the Ethno-Realistic Mathematics Education (Ethno-RME) model on improving HOTS and self-efficacy among elementary school students. This study highlights its novelty by simultaneously examining cognitive (HOTS) and affective (self-efficacy) outcomes within an Ethno-RME framework at the elementary school level, which remains underexplored in previous studies. The research employed a quantitative approach with a pre-experimental one group pretest-posttest design. The instruments consisted of a HOTS test and a self-efficacy questionnaire administered before and after the treatment. Data were analyzed concisely using multiple regression analysis to examine the contribution of Ethno-RME to both outcome variables. The subjects were 159 elementary school students in Kesambi District. The results showed a significant improvement in students’ HOTS and self-efficacy after the implementation of the Ethno-RME model based on traditional house miniatures. These findings indicate that integrating local culture into mathematics learning through a realistic approach not only enhances cognitive understanding but also strengthens students’ confidence. Therefore, the Ethno-RME model can serve as an alternative contextual learning strategy that supports the development of both HOTS and self-efficacy.